The course of inflammatory bowel disease during pregnancy and postpartum: a prospective European ECCO‐EpiCom Study of 209 pregnant women. Issue 5 (15th July 2013) - Pedersen, N.; Bortoli, A.; Duricova, D.; D′Inca, R.; Panelli, M. R.; Gisbert, J. P.; Zoli, G.; López‐Sanromán, A.; Castiglione, F.; Riegler, G.; Annese, V.; Gionchetti, P.; et al.
Summary Background The impact of pregnancy on the course of IBD is still controversial. Aim To investigate the impact of pregnancy on IBD and to search for factors with potential impact on remission. Methods Pregnant IBD women from 12 European countries were enrolled between January 2003 and December 2006 and compared at conception (1:1) with nonpregnant IBD women. Data on disease course were prospectively collected at each trimester during pregnancy and in the postpartum (6 months) using a standardised questionnaire. Results A total of 209 pregnant IBD women were included: 92 with Crohn's disease (CD; median age 31 years, range 17–40) and 117 with ulcerative colitis (UC; median age 32 years, range 19–42). No statistically significant difference in disease course during pregnancy and postpartum was observed between pregnant and nonpregnant CD women. Longer disease duration in CD and immunosuppressive therapy were found to be risk factors for activity during pregnancy. Pregnant UC women were more likely than nonpregnant UC women to relapse both during pregnancy (RR 2.19; 95% CI: 1.25–3.97, 0.004) and postpartum (RR 6.22; 95% CI: 2.05–79.3, P = 0.0004). During pregnancy, relapse was mainly observed in the first (RR 8.80; 95% CI 2.05–79.3, P < 0.0004) and the second trimester (RR 2.84, 95% CI 1.2–7.45, P = 0.0098). Conclusions Pregnant women with Crohn's disease had a similar disease course both during pregnancy and after delivery as the nonpregnant women. In contrast, pregnant women with ulcerative colitis were at higher risk of relapse during pregnancy and in the postpartum than nonpregnant ulcerative colitis women.